Models of leadership in information technology projects - Yousef A. Baker, El-Ebiary; Mohd Hafiz, Yusoff@Che Abdullah; Waheeb, Abu-Ulbeh (2020)
The present study contains an empirical effortcarried out to identify the successful styles of leadership for those managing the Information Technology/Systems projects (i.e., managers). The aptness of transformational leadership alongside other critical success factors was examined in this work, and the attained outcomes demonstrate that the behaviours associated with transformational and technical leadership existing in combination appears to change the effectiveness of transactional leadership, leading to greatsuccess of project. Notably, a specific style of leadership that is considered as fitting for every context of project is yet to be discovered. Hence, to improve the effectiveness of leadership, the present study recommends the application of a style which ischaracterised by behavioural charisma, intellectual stimulation, organisational catalyst, and behaviours of contingent reward.